On the theory of convergence and compactness for Beltrami equations with constraints of set-theoretic type - Lomako, T.V. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
We prove theorems on convergence and compactness for classes of regular solutions of degenerate Beltrami equations with set-theoretic constraints imposed on the complex coefficient and construct variations for these classes.